1995
DOI: 10.1128/jb.177.18.5316-5321.1995
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of lipooligosaccharides from Haemophilus ducreyi ITM 5535, ITM 3147, and a fresh clinical isolate, ACY1: evidence for intrastrain heterogeneity with the production of mutually exclusive sialylated or elongated glycoforms

Abstract: The structures of the lipooligosaccharides (LOSs) from Haemophilus ducreyi ITM 5535 and ITM 3147 and a fresh clinical isolate, ACY1, have been investigated. Oligosaccharides were obtained from phenol-waterextracted LOS by mild acid hydrolysis and were studied by methylation analysis, fast atom bombardment and electrospray ionization mass spectrometry, and nuclear magnetic resonance spectroscopy. The major oligosaccharide obtained from all strains was a nonasaccharide with the structure ␤-D-Galp- (134)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…In addition, Melaugh et al [10] reported that a di-LacNAc glycoform was also present at very low abundances in strain 35000. A similar observation was reported by Schweda et al [14] for several clinical isolates. The di-LacNAc pathway appears to compete with a more dominant biosynthetic pathway that adds sialic acid, effectively capping the extension of the oligosaccharide branch [10].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…In addition, Melaugh et al [10] reported that a di-LacNAc glycoform was also present at very low abundances in strain 35000. A similar observation was reported by Schweda et al [14] for several clinical isolates. The di-LacNAc pathway appears to compete with a more dominant biosynthetic pathway that adds sialic acid, effectively capping the extension of the oligosaccharide branch [10].…”
supporting
confidence: 76%
“…To obtain LOS-glycoforms that are more suitable to ESI-MS/MS under positive-ion conditions, the O-deacylated LOS glycoforms were treated with aqueous HF (4°C, 12 h) 2), which gave structural proof that a terminal sialic acid residue was added to the terminal LacNAc moiety. The presence of the abundant sialylated di-LacNAc species (A' 5 b 2 a 1 ) was of considerable interest, as the di-LacNAc species has been reported to be present in wild type strains but not the sialylated counterpart [14]. To obtain unambiguous data for this sialylated diLacNAc glycoform, an ESI-MS/MS spectrum was re- …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that H. ducreyi LOS cause ulcers in rabbits and mice (9,21,55). Recent structural studies have begun to define the LOS glycoforms expressed by several different H. ducreyi strains, including strains 35000, ITM5535, ITM3147, and ACY1 (27,29,45). In addition, recent data have demonstrated that the principal LOS glycoform expressed by most H. ducreyi strains is highly sialylated on the terminal galactose residue of N-acetyllactosamine in a manner similar to that previously reported for Neisseria gonorrhoeae (27; reviewed in reference 39).…”
mentioning
confidence: 79%
“…GC-MS of the partially permethylated alditol acetates established the presence of four sugars: a terminal glucose and terminal heptose, a 2-linked heptose, and a 3,4-linked heptose. The absence of 2-keto-3-deoxyoctulosonic acid (Kdo) was expected due to the conversion of the presumed 4-phospho-Kdo sugar to the anhydro-Kdo products during the mild-acid step (6) as reported previously for several Haemophilus species (34,35,45,46), including the LOS from the parental H. ducreyi 35000 (28,29). These reducing terminal anhydro-Kdo diastereomers are presumably destroyed during the acid hydrolysis conditions used in the monosaccharide analysis.…”
Section: Identification Of Tn916 Mutants Deficient In Los Biosynthesismentioning
confidence: 99%
“…In order to increase our understanding of the role of LOS in the pathogenesis of chancroid, the structures of the major glycoforms of the LOS from H. ducreyi strains have been determined (8,28,29,41,42). The major glycoform from strain 35000HP has the following structure: Gal␤134GlcNAc␤13 3Gal␤134Hep␣136Glc␤13(Hep␣132Hep␣13)3,4Hep␣13 5Kdo.…”
mentioning
confidence: 99%